Locking Reconstruction Plate for the Management of Diaphyseal Femoral Fracture in a Dog - V, Vijay Kumar; M, Shiju Simon; H, Pushkin Raj; R, Mahesh; S, Ayappan (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Fracture of the long bone is a commonly encountered orthopaedic problem in canine practice (Aithal et al.,1999). Femur fractures are one of the most common orthopaedic affections encountered in dogs comprising 35 %  of hind limb fractures and 24 %of all fractures in dogs (Johnson et al., 1998). Proximal and distal epiphyseal fractures happen in young animals, whereas diaphyseal and metaphyseal fractures are more frequent in older animals(Guiot et al., 2012, Abd El Raouf, 2017). They are difficult to repair due to the fact that such dogs are recumbent and need early rehabilitation to establish speedy recovery. The closeness of the abdominal wall to the proximal femur and surrounding heavy muscles limits the use of coaptation and external skeletal fixation for femoral fractures.